Assessing Appropriate Punishment (International Journal of Innovative Research in Engineering & Management, 2021)
Uniform though a prisoner has the right to request, condemning is often seen as the most significant and last stage of the  criminal justice system. It has the psychological impact of  bringing justice to a satisfactory conclusion. However, the fact  that in our country, the assessment of suitable punishment is  based mostly on imprecise phrases such as aggravating or  mitigating conditions or severity do not serve the aim of  criminal justice administration. It's considered ambiguous  because what one judge finds aggravating or extenuating need  not/will not be the same for another. Few Committee Reports  have proposed the laying of systematic guidelines to solve this  problem. The purpose of this article is to highlight the current  method for determining appropriate punishment, as well as the  necessity for organized sentencing guidelines based on judicial  precedents and Committee Reports. The study concludes that,  in order to avoid this disparity in sentencing, the judiciary must  establish a clear set of guidelines for sentencing policies, as  well as “ For particular actions that do not need the ultimate  sentence but do necessitate a more serious sentence, life  incarceration with repentance or release.
Keywords: Convict; Punishment; Precedents; Remission; Vague